Theory of planned behavior explains males' and females' intention to receive COVID-19 vaccines differently - Kai Dou; Jin Yang; Lin-Xin Wang; Jian-Bin Li (Taylor & Francis Group, 2022)
Uptake of COVID-19 vaccines is an important measure to curb the transmission of the coronavirus. Before the vaccines were available, numerous studies found that people had a moderate-to-high intention to receive the vaccines. Several studies have also used the theory of planned behavior (TPB) to predict people's COVID-19 vaccination intention with three elements (i.e. attitudes, subjective norms, and perceived behavioral control) . However, the vaccination rate falters after the vaccines became available, and there were few updated data documenting people's vaccination intention and how well TPB can explain their intention. In addition, studies investigating other outcomes found that the predictive utilities of TPB often varied across gender, but such gender differences received little consideration in the literature of COVID-19 vaccination intention. To help fill these gaps, we examined the associations between TPB elements and people's intention to receive COVID-19 vaccines and the moderation of gender in the context of vaccination campaign. Participants were 405 Chinese citizens. They reported on the three TPB elements and intention to receive vaccines in the coming months. Descriptive results showed that participants' vaccination intention was moderate. Results of path analysis showed that subjective norms and perceived behavioral control were positively related to vaccination intention for the whole sample. Furthermore, results of multigroup path analysis showed that attitudes were only related to males', while subjective norms were only related to females', intention. These findings enhance the utility of TPB in explaining people's COVID-19 vaccination intention and inform gender-specific strategies to boost males' and females' vaccination intention.